Elaboração e Validação de um Banco de Expressões Faciais de Bebês - Nascimento, Iza Neves de Araújo (2016)
Facial expressions are an important way of non-verbal communication present in interpersonal relations. Many studies has sought to understand the emotional, cognitive and social developments through the analysis of the expression and perception of facial expressions. Nevertheless, there are still few studies regarding this matter in the first childhood. The objective of this study was to prepare and validate a facial expression database of babies ranging from 4 to 24 months. This is a descriptive, exploratory and transversal study with a quantitative methodological approach and it was divided in three stages. In the first, we captured photographs of the facial expression of 30 babies to the respective emotions: happiness, sadness, disgust, pain and neutral face. In the second stage, from a collection of 240 pictures, four referees selected 80 images of 16 babies (eight boys and eight girls) to be evaluated in the next phase of the study. The third stage involved the validation of the facial expressions by 150 puerperal women, divived in two groups: 75 primiparous and 75 multiparous with a mean age of 25.6 years (SD = 5.67). They had an eutocic parturition in a public hospital and were hemodynamically stable. In this task, the subjects should identify the facial emotion of each image of the babies in accordance with the previous stated categories (happiness, sadness, disgust, pain and neutral face). The data analysis didn’t showed any significant differences between the primiparous and multiparous mothers in the recognition of facial expressions. Our data showed that the happiness and neutral face facial expressions were better recognized with a respective recognition mean of 85.3% (SD = 1.2) and 87% (SD = 1.5).Sadness was the less recognized emotion with mean of 51.1% (SD = 1.4). There were no significant statistical interaction between the sex of the model and parity. However, there was a significant statistical interation between the facial expressions and sex, showing that the facial expressions of pain and neutral face were better recognized than the rest for the masculine models when compared to the feminine (p<0.001) and, the disgust facial expression of the feminine models had a recognition mean larger than the masculine models (p<0.001). The relation between the recognition of facial expressions and maternal age showed that, as age progresses, the recognition of multiparous mothers increase for disgust and the recognition of primiparous mothers increase for pain. In the process of validation, three models of the facial expressions database were excluded due to reduced indices (<40%) to the recognition of at least one emotion. Thus, our babies facial expression database included 65 pictures of 13 models: 6 feminine and 7 masculine, with high indices of recognition in the facial expression task.